Utility of Broca’s Index in Assessing Body Mass: Analysis of Anthropometric Measures from a Cross Sectional Study - Mundodan, Jenyz M; C R Saju; Joshy, Vidhu M (National Journal of Community Medicine, 2019)
Introduction: Broca’s index is the easiest method to calculate the ideal body weight for height. However, the absence of a defined range limits its utility. This study aims to identify ‘normal range’ for Broca’s index that corresponds to the normal range for BMI and to determine the predictive accuracy for cut-off points thus obtained. Methods: Anthropometric measurements of adults were taken during a cross sectional survey. BMI and ideal weight as per Broca’s Index were calculated for each individual. Broca’s Index Ratio was calculated as the ratio of actual weight to the calculated Broca’s Index (ideal weight). ROC curves were plotted to identify the best cut off points for Overweight and obesity. Results: The BMI of the participants ranged from 16.14 to 35.16, with a mean 25.53 kg/m2 (SD=2.86). Broca’s index ratio had strong correlation with the BMI value (r=0.969). From the ROC curves, Broca’s Index ratio against BMI values of 23 and 25 were identified as 0.95 and 1.03. Broca’s Index ratio of 1 corresponds to BMI Value 24.01. Conclusions: Individuals can be advised on their ideal weight (as per Broca’s index), with the upper limit being around 5% less than the calculated value.